Penglibatan Pelajar dan Motivasi Pelajar sebagai Peramal Kepuasan Pembelajaran di Ruang Pembelajaran Hibrid Segerak - Ying-Leh Ling; Wen Wen Chua (Journal of Education on Social Science (JESS), 2023)
A synchronous hybrid learning space combines traditional on-site and online learning into a single learning experience to promote effective learning for both on-site and online students concurrently. It is a flexible, accessible, and engaging learning environment. There is a dearth of research on the factors that influence synchronous hybrid learner learning satisfaction as compared to traditional on-site or online learning environments. The relationship between student engagement, student motivation with student learning satisfaction in synchronous hybrid learning space was underexplored although these student learning competencies were noticeably strong predictors of student learning satisfaction in the full on-site or online settings. Hence, this study aimed to explore predictive learning competencies for student learning satisfaction in synchronous hybrid learning. A cross-sectional method was employed to collect quantitative data from 169 students of a Technical and Vocational Education and Training (TVET) institute located in Kuching, Sarawak at a given point in time. These respondents’ learning competencies and learning satisfaction in synchronous hybrid learning spaces were investigated. The research findings showed that student engagement (i.e., emotional, cognitive, and behavioural) and student motivation (i.e., intrinsic goal orientation, extrinsic goal orientation, and self-efficacy) which are found predictive in traditional on-site and online learning settings can be applied in synchronous hybrid learning space as well. The results of this study were intended to guide practices and policies related to the design and implementation of synchronous hybrid learning to add value and further substantiate the potential of this learning space.